THE COMPETENCE OF THE PHYSICAL EDUCATION TEACHER CONCERNING GENDER APPROACH IN THE PROCESS OF TEACHING - Zaikin, A. V.; Shenknekht, N. M. (Вісник Кам’янець-Подільського національного університету імені Івана Огієнка. Фізичне виховання, спорт і здоров’я людини, 2015)
In the article gender competence suggests the formation of a lecturer or a teacher understanding of men’s and women’s role in society, its status, functions and relationships, the ability of the critical analysis of its activity as the representative of a certain gender, as well as knowledge about gender features of subjects of the educational process and other aspects of gender pedagogy.